Comparison of adverse reactions of spiramycin versus pyrimethamine/sulfadiazine treatment of toxoplasmosis in pregnancy: is spiramycin really the drug of choice for unproven infection of the fetus - Prasil, Petr; Sleha, Radek; Kacerovsky, Marian; Bostik, Pavel (Journal of maternal-fetal & neonatal medicine, 2023)
BACKGROUND: Therapeutic regimens for the treatment of toxoplasmosis are not standardized. Treatment strategy mainly at the end of the second and the beginning of the third trimester, especially in cases of negative prenatal diagnosis, is the least uniform. In some situations, the choice of treatment may be ambiguous, and adverse drug reactions of the therapy should be taken into consideration. METHODS: Adverse drug reactions of anti-toxoplasma therapy with spiramycin (n = 77) versus pyrimethamine/sulfadiazine (n = 35) were compared in 112 pregnant women. RESULTS: Up to 36.6% of women reported adverse reactions to the treatment overall (n = 41). Out of those 38.9% (n = 30) were treated with spiramycin and 31.4% (n = 11) with pyrimethamine/sulfadiazine. Toxic allergic reactions were the only indication for discontinuation of treatment in 8.9% of patients (n = 10), where 9.1% (n = 7) were reported in spiramycin and 8.6% (n = 3) in pyrimethamine/sulfadiazine cohort. Neurotoxic complications (acral paraesthesia) were significantly more frequent during the therapy with spiramycine in 19.5% (n = 15) compared to no cases in pyrimethamine/sulfadiazine group (p = .003). Other adverse drug reactions, such as gastrointestinal discomfort, nephrotoxicity, vaginal discomfort were reported, but the differences between the cohorts were not significant. CONCLUSIONS: The superiority of one of the therapeutic regimens was not statistically demonstrated, since the differences in overall toxicity or incidence of toxic allergic reactions between the cohorts were not confirmed (p = .53 and p = 1.00, respectively). However, although the isolated neurotoxicity of spiramycin was the only significant adverse reaction demonstrated in this study, pyrimethamine/sulfadiazine therapy should be preferred, because it is known to be more effective and with limited adverse reactions.
Keywords: těhotenství; lidé; Drug Therapy, Combination; Pyrimethamine; Female; kombinovaná farmakoterapie; Humans; Toxoplasmosis, Congenital; Fetus; Sulfadiazine; pyrimethamin; alergie; spiramycin; Drug-Related Side Effects and Adverse Reactions; Pregnancy; ženské pohlaví; toxoplazmóza; sulfadiazin; nežádoucí účinky léčiv; plod; Hypersensitivity; Toxoplasmosis; Spiramycin; kongenitální toxoplazmóza